Harmonization of Customary Law and Islamic Law in the Zereah Tradition of Marriage in Hiang Tinggi Village: A Maqasid al-Shariah Perspective - Risna Ayu Lestari; Widiya Yul (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study examines the Zereah tradition as a post-marriage customary practice and analyzes its role in harmonizing Islamic law and customary law through the maqasid al-shariah framework. The tradition functions to reinforce kinship ties, introduce newlyweds to the wider community, and ensure social legitimacy. It involves symbolic elements such as traditional attire, communal prayers, and marital advice, reflecting the integration of cultural and religious values. While previous studies have primarily emphasized the formal-legal aspects of the marriage contract, this research highlights the customary sphere as a crucial space for the social contextualization of Sharia. Employing a qualitative empirical design with normative-theological and socio-legal approaches, data were collected through observation and in-depth interviews with married couples, customary and religious leaders, and community members. Secondary sources included fiqh literature on maqasid al-shariah and ‘urf, marriage legislation, and related studies. Data were analyzed using the interactive model with source triangulation to ensure validity.The findings reveal that Zereah is practiced in a simple and non-coercive manner, involving symbolic offerings such as cigarettes, sweets, and betel wrapped in a sarong, while the couple often receives rice or monetary support, reflecting communal solidarity. From an Islamic legal perspective, the tradition qualifies as ‘urf sahih and promotes maslahah. Within the maqasid al-shariah framework, it supports the preservation of religion, life, intellect, lineage, and wealth. The study’s novelty lies in conceptualizing Zereah as a model of dialogical legal harmonization that operationalizes Sharia objectives and strengthens the socio-normative legitimacy of marriage.